The Use Of Learning Technology In Elementary School - Fitriyati, Fina; Dwi Utari, Mutia; Maulida Astuti, Utami; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
In the advance of the times in the era of revolution in the 4.0 era was one of the greatestchallenges facing teachers in Indonesia. Because the quality of education has become arefusal to measure the success of the younger generation in the face of the era of revolution4.0. A teacher in this age must embrace technology, for a teacher who is devoid or less ofknowledge of technology cannot instil in his students the critical power to become arevolutionary human being. This paper discusses the literature of technology utilization ineducation. The teacher and the pupil have the ability and knowledge in the field ofinformation technology. The various technological tools teachers use in school visits amongothers, LCDs, laptops, computers and so on. To be a teacher with knowledge of technologymust also be supported by the government through training, socialization, seminars.